Nucleotide sequence of a bean (Phaseolus vulgaris) U1 small nuclear RNA gene: implications for plant pre-mRNA splicing. - van Santen, V L (1987)
We have isolated a U1 small nuclear RNA (snRNA) gene from common bean (Phaseolus vulgaris). The haploid bean genome contains only one or a few copies of the U1 snRNA gene. The bean and human U1 snRNA genes are 65% homologous but share no significant similarity in the 5' or 3' flanking regions. The predicted secondary structure of bean U1 snRNA is identical to that of other U1 snRNAs, and the sequences of the single-stranded regions have been highly conserved. Thus, both the sequence of the single-stranded regions and the secondary structure of U1 snRNA appear to be important for its function. The role of U1 snRNA in pre-mRNA splicing is probably similar in plants and animals.